Conservative treatment in Scheuermann's kyphosis: comparison between lateral curve and variation of the vertebral geometry. Issue 2 (October 2016) - Aulisa, Angelo; Falciglia, Francesco; Giordano, Marco; Mastantuoni, Giuseppe; Poscia, Andrea; Guzzanti, Vincenzo
Abstract Background Conservative treatment in the Scheuermann's kyphosis obtain, during skeletal growth, remodelling of the deformed vertebras. In a previous paper on Scheuermann's kyphosis, we have studied the geometry variations of all vertebrae included in the curve, before and after the treatment. The purpose of this study was to confirm the effectiveness of conservative treatment in Scheuermann's kyphosis and was to evaluate and compare the variation of the vertebral geometry with the curve trend in Cobb degrees, before and after conservative treatment. Methods From a consecutive series of patients, we selected 90 patients with thoracic Scheuermann's kyphosis, treated using anti-gravity brace: 59 male, 31 female. The mean age at the beginning of the treatment was 14 years. Radiographical measurements were performed on radiographs from a lateral projection, at the beginning (t1) and at the end of the treatment (t5). Vertebral geometry modifications at t1 and t5 were analysed according to the following parameters and evaluated by three independent observers: Anterior wedging angle (ALFA) of the apex vertebra and Posterior wall inclination (APOS) of the limiting lower vertebra. The curve was measured in Cobb degrees. Results The results from our study showed that of the 90 patients with a thoracic curve mean value of Cobb degrees was 57.8 ± 6.0 SD at t1 and 41.3 ± 5.6 SD at t5. The differences between t1(angle at baseline) and t5 (end of treatment) were calculated for Cobb, ALFA and APOS angle and were respectively −16.4 ± 4.5, −6.4 ± 1.4 and −2.7 ± 1.2; tested with pairedt -test were significative (p  < 0.01). The results of the regression analysis to test the relationship between the three measures for the kyphosis (Cobb degree, ALFA and APOS) showed that the best association was between Cobb t5 and ALFA t5 (p  < 0.01) and Cobb t1 and APOS t1 (p  < 0.01). No significative association was found between the difference between ALFA and APOS. Conclusion We sustain that using new parameters to study vertebral remodelling allows us to reach a better comprehension of Scheuermann spine response to anti-gravity brace treatment. Furthermore, the evaluation of the ALFA angle of the apex vertebra confirms to be more reliable than Cobb's angle because it cannot be affected by the radiological position.